AN ASSESSMENT OF THE POST-REHABILITATION (FERTILIZATION) OF COCONUT IN SCFDP FARMS, PHILIPPINES - Severino S. Magat , Ph.D (International Coconut Community Journal, 1999)
Selected sample farms (79) under the Small Coconut Farms Development Project (SCFDP, Philippines) representing five (5) regions and nine (9) provinces were evaluated. The yield trends: (1) initial or benchmark; (2) during rehabilitation period (3-4 years); and (3) post-rehabilitation period (2) years were examined using the nut and copra yield estimation method of the PCA (MAGAT, 1995). On nut yield, the benchmark average annual yield of 35 nuts/tree increased to 91 nuts/tree during the rehabilitation (rehab) period but dropped to 70 nuts/tree during the post-rehabilitation (post-rehab) period or two (2) years without fertilizer application. This 160% increase in nut production (1995) followed by a reduction of 23% at the post-rehab period is indicative of a moderate to strong residual fertilizer effect after the significant rehabilitation of palms by fertilizer application (supplying mainly N, K, Cl and S fertilizer nutrients). On copra yield, the pre-rehabilitation annual copra yield of 0.94 t ha reached 3.01 t/ha during the rehab period, followed by a drop to 2.21 t/ha at post-rehab. The copra yield increase of 220% during the rehab (1995) is mainly due to the increase in nut yield and nut size or copra weight per nut. An average reduction of 27% during the post- rehab period was observed but in some areas the yield of palms dropped close to pre-rehabilitation nut and copra levels, suggesting lower degree of fertilizer residual effects compared to other coconut regions. Implications of findings in relation to the rehabilitation by judicious fertilization of low-yielding, nutritionally-deficient non-senile palms are discussed.